[Two students in Yosemite dorm room] (1977)
Two students relax inside a Yosemite Hall room, showing a small tiled hallway through the room door, a small bookshelf on the wall with a plant, horse decorations, and a few books. A poster is hanging on the wall. One student reclines on the bed with several large stuffed animals while another student sits on the floor looking up at the other.